2015 PSRH CONFERENCE ABSTRACTS - Alec Joseph Ekeroma (Pacific Journal of Reproductive Health, 2015)
Introduction The relationship between sexuality and health is complex, with both beneficial and detrimental aspects. We examined how these associations varied by age, gender, social condition, and disability among adults in France. Methods This study draws on the CSF-2023 national survey on sexuality in France. Our analytic sample comprised 19,192 sexually active respondents aged 18-89 years. We used multivariable logistic regressions to examine associations between dimensions of sexuality (sexual activity in the past year, frequency of sex, penetrative sex, masturbation, lifetime sexual violence, sexual dysfunction, and sexual satisfaction) and three health outcomes (self-perceived health, depression, and anxiety). We tested for interactions by gender, sexual identity, partnership status, economic hardship, and disability/chronic illness. Results Over a quarter of respondents reported poor/fair health and 18% experienced symptoms of depression or anxiety. Sexual dissatisfaction and past sexual violence increased the likelihood of poor/fair health, depression, and anxiety for both genders. Other associations varied by sexuality indicator, health condition, and age. Younger respondents experienced more negative health impacts from sexual violence, while sexual inactivity was more strongly linked to depression among men over 60 years and anxiety among women over 60 years. Additionally, masturbation was only associated with decreased odds of anxiety among women over 60 years. Conclusions This study underscores the intricate relationship between sexuality and health, uncovering varying positive correlations across the life course. Considering the strong connections between health and sexual satisfaction, quality of sexual life should be part of clinical assessments as an integral component of health and well-being.